2011
DOI: 10.1371/journal.pone.0016260
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Hedgehog Signaling in Ventral Body Wall Development and the Onset of Omphalocele Formation

Abstract: BackgroundAn omphalocele is one of the major ventral body wall malformations and is characterized by abnormally herniated viscera from the body trunk. It has been frequently found to be associated with other structural malformations, such as genitourinary malformations and digit abnormalities. In spite of its clinical importance, the etiology of omphalocele formation is still controversial. Hedgehog (Hh) signaling is one of the essential growth factor signaling pathways involved in the formation of the limbs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 90 publications
(108 reference statements)
4
31
0
1
Order By: Relevance
“…The frequency of this malformation is reported to be approximately 1 in 4000 live births (Matsumaru et al, 2011), and despite this high incidence, the cause of omphalocele formation remains unclear. In addition to ).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of this malformation is reported to be approximately 1 in 4000 live births (Matsumaru et al, 2011), and despite this high incidence, the cause of omphalocele formation remains unclear. In addition to ).…”
Section: Discussionmentioning
confidence: 99%
“…Concordant recovery of the physiological umbilical hernia and the closure of pelvic girdle has been reported in genetically modified mice [23].…”
Section: Pubic Diastasis Is Normal During Embryogenesismentioning
confidence: 79%
“…Concordant recovery of the physiological umbilical hernia and closure of the pelvic girdle in genetically modified mice have been demonstrated by Matsumaru et al [23], and Cheng et al [26], established a genetic model of BEEC in p63-/-knockout mice, which showed the complete spectrum of BEEC in association with exomphalus. These studies, as well as the frequent occurrence of BEEC (especially cloacal exstrophy) with exomphalus, suggest that body wall closure and closure of the pubic arch may be interrelated.…”
Section: Scientific Evidencementioning
confidence: 81%
“…However, little information has been revealed for such caudal body formation. Genetic studies identified a few genes for the formation of the dorsal part of GT and the ventral body wall (34). Some of these genes are initially expressed in the mesenchyme adjacent to the umbilical cord.…”
Section: Epispadias and Complex Form Of Exstrophy In External Genitalmentioning
confidence: 99%